Utilization of Digital Marketing in Raising Brand and Trust for Spicy Porridge Products in Harapan Village SMEs New Sei Lepan District, Langkat Regency - Ahmad Fadli; Amin Hou; Martin; Ratih Amelia; Widy Hastuty Hs; Ester Hervina Sihombing; Sabaruddin Chaniago (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
The current problem in the production of this porridge is that sales are made only to the surrounding community. This happens because many people outside the region are not aware of the existence of the spicy porridge because no branding has been carried out and trust in the spicy porridge product is not yet strong. To overcome this, the solution offered to SME partners is by utilizing social media in building a brand image and finding the most suitable packaging through social media. These activities are carried out such as assistance in making social media and website creation, improving production management, Organizing Focus Group Discussion (FGD) activities in the form of socializing the use of social media, utilizing Viral Marketing social media by uploading as often as possible related to spicy porridge products and finally Hastag services. and Google Trends can be part of a strategy to increase sales. The results of the activity can be concluded that (1) this PKM activity is successful, it can increase the understanding of SME partners in utilizing information technology such as social media in building a brand image, (2) In solving problems related to porridge packaging, SME partners have been able to find attractive packaging with utilizing social media and (3) PKM activities are found to be fun and in accordance with their objectives, and participants will feel happier if this activity is continued with collaboration between the service team and SME partners.